Pediatric patients with familially inherited sitosterolemia: Two case reports - Su, Shun-Qing; Xiong, Di-Sheng; Ding, Xiu-Mei; Kuang, Jin-An; Lin, Yue-Chun (Frontiers in Cardiovascular Medicine, 2022)
Background: Sitosterolemia is a rare recessive genetic abnormality of hyperlipidemia; it is characterized by increased levels and accumulation of sitosterol in the plasma and local tissues. Case descriptions: The study subjects were two siblings (brother and sister) who had sitosterolemia with systemic multiple xanthomas as the main manifestation. The main clinical manifestations were hypercholesterolemia, premature atherosclerosis, arrhythmia, systemic multiple xanthomas, etc. After genetic testing, it was found that the patients had a compound heterozygous mutation of c.1324+1de1G in exon 7 and exon 9 of chromosome 2p21 of the adenosine triphosphate binding cassette transporter G family member 5(ABCG5) gene; the mutation at c.904+1G>A was of maternal origin, and the mutation at c. 1324+1de1G was of paternal origin. The compound heterozygous mutation of these two genes led to a metabolic disorder of plant sterols in vivo. Conclusion: Sitosterolemia is an autosomal recessive disease that could be effectively controlled after dietary control and oral lipid-lowering therapy with Ezetimibe. Xanthomas, which affects function and appearance, could be surgically removed, and primary wound healing could be achieved.